Sella turcica morphometrics in subjects with down syndrome - Papaefthymiou, Petros (My University, 2022)
Amaç: Bu çalışmanın amacı, Down sendromlu bireylerde sella tursikanın boyut ve şeklini morfometrik yöntemler uygulayarak sağlıklı kontrol grubu ile karşılaştırmaktır. Gereç ve Yöntem: Bu retrospektif çalışmada, Marmara Üniversitesi, Diş Hekimliği Fakültesi, Ortodonti nda (İstanbul, Türkiye) muayene edilmiş 24 Down sendromlu bireyin arşiv kayıtları, yaş ve cinsiyet açısından eşleştirilmiş 24 sağlıklı birey karşılaştırılmıştır. Toplanan sefalometrik radyograflar Nemoceph (Nemotec, Madrid, İspanya) yazılımına yüklenmiş ve analizden önce magnifikasyon oranları ayarlanmıştır. Sella anterior, orta nokta ve posterior yükseklik gibi parametreler ölçülmüş, ayrıca sella genişliği, alanı ve uzunluğu hesaplanmıştır. Sella tursikanın geometrik morfometrik analizi, Viewbox 4 sefalometrik yazılımı (dHAL Software, Kifissia, Yunanistan) ile, Procrustes metoduyla çakıştırma ve temel bileşen analizi (PCA) gibi yöntemler uygulanarak yapılmıştır. İstatistiksel anlamlılık p<0,05 olarak belirlenmiştir. Bulgular: Sella anterior yüksekliği, sella orta nokta yüksekliği, sella maksimum yüksekliği ve sella alanı ile ilgili olarak Down sendromlu bireyler ve sağlıklı kontrol grubu arasında istatistiksel olarak anlamlı farklılıklar bulunmuştur. Yukarıda bahsedilen tüm değerler Down sendromlu bireylerde istatistiksel olarak anlamlı ölçüde artmıştır (p<0,05). Temel bileşen analizi, Down sendromlu bireyler ve sağlıklı kontrol grubu arasında sella şeklinde istatistiksel olarak anlamlı bir farklılık ortaya koymuştur (p<0,05). Sonuç: Down sendromlu bireyler, sağlıklı kontrol grubuna kıyasla anlamlı şekilde artmış sella tursika boyutları ve istatistiksel olarak anlamlı şekil farklılıkları göstermiştir.

Objective: The aim of the present study is to implement morphometric methods to investigate the size and shape of sella turcica in subjects with Down syndrome. Material and Methods: In this retrospective study, archive records of 24 individuals with Down syndrome examined at Marmara University Faculty of Dentistry, Department of Orthodontics (Istanbul, Turkey) were compared to 24 non-syndromic individuals matched for age and gender. The collected cephalometric radiographs were loaded into the Nemoceph (Nemotec, Madrid, Spain) software and adjusted for magnification prior to analyzing. Parameters such as sella anterior, midpoint, and posterior height were measured, as well as sella width, area, and length were calculated. Geometric morphometric analysis of the sella was performed with Viewbox 4 cephalometric software (dHAL Software, Kifissia, Greece), implementing methods such as Procrustes superimposition and principal component analysis. Statistical significance was set at p<0,05. Results: Results: Statistically significant differences were found for sella anterior height, sella midpoint height, sella maximum height, and sella area. All the aforementioned values were significantly increased in the Down syndrome subjects (p<0,05). Principal component analysis (PCA) depicted a statistically significant difference in sella shape between patients with Down syndrome and healthy controls (p<0,05). Conclusion: Subjects with Down syndrome presented significantly increased sella turcica dimensions as well statistically significant differences in shape compared to healthy controls.
Keywords: Cephalometric radiography; Down sendromu; Down syndrome; Genetics; Genetik Sella turcica; Geometric Morphometrics; Geometrik morfometrik; Orthodontics; Ortodonti; Sefalometrik radyografi; Sella turcica